A pilot study of constipation among the elderly in Hospital Universiti Sains Malaysia - Abdul Wahab, Patimah; Mohd Yusoff, Dariah (2014)
Background: Older people are susceptible for constipation, resulting in high prevalence particularly among those who are hospitalized. Poor mobility and longer stay in hospital are some of the indication for constipation to occur among them. Thus, understanding of its health-related impact among hospitalized elderly is essential for early identification and management of chronic constipation.